The Logic of The Market versus The Logic of Social Work: Whither the Welfare State? - Mimi Abramovitz; Jennifer Zelnick (Social Work & Society, 2019)
Privatization, a well-known Neoliberal strategy, is transforming the human services in both Europe and the US. Scholars have studied its impact on clients, the hollowed out welfare state, and the economic slowdown. Few have examined how privatization within agencies - better known as Managerialism/New Public Management--affects service provision, the organization of work, and the well being of the workforce. Filling this gap this research: 1) describes three overlapping historical phases of privatization in US human services: Marketization, Managerialism and Financialization; 2) analyzes how 3000 front line workers view the impact of Managerialism in their agencies, and 3) applies the lens of race to the findings. An anonymous electronic survey was distributed 3000 NYC human service workers in collaboration with five major human service organizations, one union, and the NY Non Profit Press. Findings suggest that human service workers--mostly women and persons-of-color-- are deeply troubled by the pressure to increase productivity, accountability and efficiency; the focus on quantifiable outcomes, and the associated dwindling of advocacy and social justice. The implications for service quality, staff retention, professional autonomy, burnout, and structural racism are explored. The finding should strengthen the voice of human service workers in the highly contested privatization debate and help to mobilize them for policy change in the welfare "service" state.